HUBUNGAN SELF-EFFICACY GURU SMA BANDUNG DENGAN IMPLEMENTASI PEMBELAJARAN BIOLOGI BERDASARKAN KURIKULUM 2013 DAN SELF-EFFICACY SISWA - Sianipar, Yanthi (2014)
Level of self-efficacy is one thing that should be considered in the process of learning biology, especially with the change in the curriculum. The purpose of this study to reveal the relationship between teacher's self-efficacy with implementation of studying biology based on curriculum 2013, the relationship between teacher's self-efficacy with student's self-efficacy and to obtain information about the readiness of the biology teacher's in implementing the curriculum 2013. This research method is the correlation method. Subjects in this study were 14 high school biology teachers at X MIA Bandung who taught in the second semester of the academic year 2013/2014 were selected at random. Total students of all teachers are 423 students. Data obtained through semantic differentiation scale self-efficacy of teachers, semantic differentiation scale student self-efficacy, suitability sheet semantic differentiation scale teacher's with semantic differentiation scale students about their teachers, rubric lesson plans, learning activities observation, interview and test students' mastery of concepts. Before learning activities going on, teachers and students are given a semantic differentiation scale self-efficacy of teachers, semantic differentiation scale self-efficacy of student and semantic differentiation scale self-efficacy students about their teachers. Based on the results of semantic differentiation scale suitability scores of teachers and students, the teacher selected purposively to be observed during the learning activities biology. Learning activities recorded in the observation sheet. After learning activities, students are given a set of multiple choice questions and conducted interviews with teachers and students. The results showed that: (1) the level of senior high school teacher's self-efficacy belong to the medium category, (2) the level of student's self-efficacy classified in the high category, (3) self-efficacy of teachers does not affect the quality of planning learning activities, (4) teacher's self-efficacy have relationships that are medium level with implementation of learning through scientific approach (r = 0.417, α = 0.05), (5) self-efficacy of teachers have a weak connection with implementation of authentic assessment (r = 0.063, α = 0, 05), (6) self-efficacy of teachers contribute to the formation of student's self-efficacy, (7) teacher's self-efficacy contribute to the achievement of student learning outcomes, (8) the presence of a positive and significant relationship between student's self-efficacy and student's achievement in studying biology (r = 0.193, p <0.05).